RELATIONSHIP PATTERNS OF INDONESIA-EGYPT DIPLOMACY THROUGH THE PONDOK MODERN DARUSSALAM GONTOR WITH AL-AZHAR UNIVERSITY - Aprilia Restuning Tunggal (Journal of Islamic World and Politics, 2020)
Egypt is the first country in the world to recognize Indonesia's independence. Egypt was also the first country to sign a treaty of friendship with Indonesia. Relations between Indonesia and Egypt have been established since before the independence of the two countries, even before diplomatic relations between the two countries. That is by sending Indonesian students who want to study at Al-Azhar University which is the tower of science, thought, culture that has a special attraction for the world. Besides that the determination of Al-Azhar in holding the principle of Wasathiyah and justice has inspired the concept of Islamic education in various levels, starting from public and private educational institutions including Islamic boarding schools. Diplomatic relations between the two countries must always be well maintained and are expected to have a positive impact on the progress of education in Indonesia. The purpose of this article is to describe the diplomatic strategy used by Pondok Modern Darussalam Gontor as a non-state actor in international relations with Al-Azhar University in education sector. This type of research is descriptive qualitative by taking the location of research in Pondok Modern Darussalam Gontor Ponorogo and Embassy of the Arab Republic of Egypt in Jakarta. Data collection techniques in this study through interviews, observation and documentation with relevant interviewees. The data analysis technique used in this study by collecting data (data collecting) from primary data and secondary data. Primary data has taken from interview and original document while secondary data is obtained from books, journal and news. The researcher will draw conclusions by focusing on the Pondok Modern Darussalam Gontor diplomacy strategy in the field of education where Gontor has received additional quota for students scholarship who will study at Al-Azhar University in Cairo Egypt. And the output of this research will be presentation in the International Conference and published in the Journal accredited by Sinta and National accredited Journal.